Governing Councils and Development of Tertiary Education in Nigeria - Ogunode, Niyi Jacob (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This paper discussed challenges militated against development of governing councils of tertiary institutions in Nigeria. Secondary data were employed in the paper. The secondary data were collected from print and online publications. The paper concluded that political instability, poor knowledge of tertiary institutions management, poor capacity building programme, strike actions and, lack of adequate research on governing council activities are challenges that militated against development of governing council of tertiary institutions in Nigeria. The paper, hereby recommended that; Federal and State government should always isolate governing councils’ of tertiary institutions from dissolution whenever they think do that. Federal and State government should limit appointment of tertiary institutions governing council to only professionals in tertiary education management and administration. Governing Councils members of tertiary institutions should always be exposed to training and retraining programme on the affairs of tertiary institutions and on how to contribute to the development of the institutions. Government should address issues responsible for strike actions in the tertiary institutions. Tertiary institutions in Nigeria should research more on how to advance activities governing council to develop the tertiary institutions and specialized training institutions should be established to cater for the development of governing councils of tertiary institution.